2020
DOI: 10.1038/s41598-020-62022-x
|View full text |Cite
|
Sign up to set email alerts
|

Automatic optic nerve head localization and cup-to-disc ratio detection using state-of-the-art deep-learning architectures

Abstract: Computer vision has greatly advanced recently. Since AlexNet was first introduced, many modified deep learning architectures have been developed and they are still evolving. However, there are few studies comparing these architectures in the field of ophthalmology. This study compared the performance of various state-of-the-art deep-learning architectures for detecting the optic nerve head and vertical cup-to-disc ratio in fundus images. Three different architectures were compared: YOLO V3, ResNet, and DenseNe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In the field of DL, there are two types of research related to the optic disc: one is related to the detection of the optic disc in the whole fundus image (19) and the other is related to the classification of the optic disc in the cropped image (20). While there has been much research on the optic disc classification algorithm, the target detection of the optic disc has not been thoroughly studied (21).…”
Section: Identification Location and Extraction Of The Optic Discmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of DL, there are two types of research related to the optic disc: one is related to the detection of the optic disc in the whole fundus image (19) and the other is related to the classification of the optic disc in the cropped image (20). While there has been much research on the optic disc classification algorithm, the target detection of the optic disc has not been thoroughly studied (21).…”
Section: Identification Location and Extraction Of The Optic Discmentioning
confidence: 99%
“…Park et al (21) studied and compared the performance of the most advanced DL architecture in detecting optic disc and VCDR in fundus images. The training data set was composed of 1959 eyes with normal fundus, glaucoma, and other optic neuropathy (in which VCDR >0.4 accounted for 94.3%) which were randomly divided into a training data set and a verification data set at a ratio of 9:1.…”
Section: Segmentation Of the Optic Cup And The Optic Discmentioning
confidence: 99%
“…Each bounding box label contains the following information: classification (c), box center coordinates (x, y), box width (w), and box height (h) (15). Approximately 90% (8,778) of the images were used for training purposes, and the remaining 10% (975) of the images were adopted as the testing set in the holdout method (17)(18)(19). Ivasˇic´-Kos et al (17) compared the results of the different ratios of training and testing sets (90:10 vs. 80:20) in machine learning study and found no significant difference of performance between the two ratio settings.…”
Section: Vpds and Data Acquisitionmentioning
confidence: 99%
“…Ivasˇic´-Kos et al (17) compared the results of the different ratios of training and testing sets (90:10 vs. 80:20) in machine learning study and found no significant difference of performance between the two ratio settings. Tao et al (18) and Park et al (19) used 90% of the total data set for training and 10% for testing the machine learning algorithms in their study and stated the ratio of 90:10 (training: testing) would be more effective for a traffic data set of less than 10,000 items. Furthermore, the cross-validation process was executed to include up to 30% of the total data set in the test data set.…”
Section: Vpds and Data Acquisitionmentioning
confidence: 99%
“…Wu et al [ 11 ] developed a deep learning model (BMSNet) with the YOLOv3 architecture for assisting haematologists in the interpretation of bone marrow smears for faster diagnosis and disease monitoring. Park et al [ 12 ] compared the performance of various state-of-the-art deep-learning architectures, including YOLOv3, for detecting the optic nerve head and vertical cup-to-disc ratio in fundus images. Safdar et al [ 13 ] highlighted the most suitable Data Augmentation technique for medical imaging by using YOLOv3.…”
Section: Introductionmentioning
confidence: 99%